A New Framework for Sustainable Hydropower Development Project - Kartina, Johan; Faiz, Mohd Turan; Nur Syazwani, Abdul Gani (IOP Publishing, 2018)
This project studies on the establishment of a new framework for sustainable hydropower development. A hydropower development is listed as one of the prescribed activities under the Environmental Quality Order 1987. Thus, Environmental Impact Assessment (EIA) guidelines must be referred to comply with the Department of Environment (DoE) requirements. In order to execute EIA, an assessment tool that will be utilized in the final evaluation phase must be determined. The selected assessment tool that will be used is Systematic Sustainability Assessment(SSA) which is a new integrated tool to evaluate the sustainability performance. A pilot run is conducted in five different departments within the Energy Company to validate the efficiency of the SSA tool. The parameters to be evaluated are constructed aligned with the Sustainable Development Goals (SDG) to maintain the sustainability features. Consequently, the performance level of the sustainability with respect to People, Planet and Profit (3P’s) is able to be discovered during evaluation phase in the hydropower development for continuous improvement.